Effects of crotamine in human prostate cancer cell line - Alberghini-dos-Santos, João Victor; Sanchez, Caroline Andolfato; Bordon, Karla de Castro Figueiredo; Pucca, Manuela Berto [UNESP]; Antunes, Lusânia Maria Greggi; Arantes, Eliane Candiani; Oliveira, Isadora Sousa de (Elsevier, 2024)
Our study presents the anticancer potential of crotamine from Crotalus durissus terrificus in human prostate cancer cell line DU-145. Crotamine isolation was conducted through RP-FPLC, its molecular mass analyzed by MALDI-TOF was 4881.4 kDa, and N-terminal sequencing confirmed crotamine identity. Crotamine demonstrated no toxicity and did not inhibit migration in HUVEC cells. Although no cell death occurred in DU-145 cells, crotamine inhibited their migration. Thus, crotamine presented potential to be a prototype of anticancer drug.
Keywords: Anticancer; CPP; Crotalus durissus terrificus; DU-145; Snake venoms